Studies of potential plant parts of Kesinai (Streblus asper) for protease production - Kua Lay Chim (School of Bioprocess Engineering, University Malaysia Perlis, 2012)
A study was carried out to study the potential plant parts of Kesinai (Streblus asper) for protease production . The potential parts of Streblus asper such as leaves, stem barks, and twigs were collected and used as a source for extracting protease enzyme. The enzyme was extracted by using phosphate buffer and distilled water at pH 7. The crude enzyme extract was tested for protease assay and casein was used as a substrate. The absorbance of crude enzyme was detected by using GENESYS 20 spectrophotometer at 660 nm since the released of tyrosine developed a blue coloration. The protease activity can be calculated from the absorbance by compared with calibration curve.